Pengaruh Sistem Pengendalian Internal Pemerintahan, Good Governance, Kompetensi Aparatur Desa, dan Job Rotation terhadap Pencegahan Korupsi dalam Pengelolaan Dana Desa - Febiyanti Indah Putri, Ni Putu Anggi; Prayudi, Made Aristia; Putra, Putu Yunartha Pradnyana (Universitas Pendidikan Ganesha, 2025)
This study aims to examine the internal government control system (SPIP), good governance, competence of village officials, and job rotation on corruption prevention in village fund management in Klungkung Regency. This study uses a quantitative approach with instruments in the form of questionnaires. The population in this study is the village apparatus in Klungkung Regency. The sample was determined by the convenience sampling method so that 98 respondents were obtained from a total population of 769 people. The data analysis techniques used include descriptive analysis, data quality test, classical assumption test, multiple linear regression analysis, and hypothesis test using SPSS version 25. The results of the study show that the internal control system of government, good governance, and job rotation have a positive and significant effect on corruption prevention. Meanwhile, the competence of village officials has a negative and significant effect on corruption.